Review of Commercially Available Epilepsy Genetic Panels. Issue 2 (5th November 2015) - Chambers, Chelsea; Jansen, Laura A.; Dhamija, Radhika
Abstract: Next generation sequencing panels have revolutionized the diagnostic approach to patients with epilepsy. There are several commercial epilepsy panels available. We assessed the list of genes tested and consent forms for epilepsy panels available at seven laboratories. The panels varied in the number of genes included (70–465 genes). In some panels, genes not currently associated with epilepsy were included (up to 4 % of panel content). The panels also included genes for lysosomal storage disorders (6–12 %), congenital disorders of glycosylation (0–8.5 %), metabolic disorders (3.5–34 %), neurological syndromes (18–43 %) and multisystemic genetic syndromes (6.4–21 %). Informed consents differed significantly between laboratories ranging from basic information about genetic testing and possible results to information about insurance, genetic counseling and familial testing, and incidental findings. Our findings suggest that it is important to consider the range of genes offered on epilepsy panels and their predicted phenotypes in an effort toward improving the informed consent process.